EFFECT OF ORGANIZATION COMMITMENT, WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE (Study at. PT. PLN (Persero) P3b Sumatera UPT Padang) - Amri, Andi; Ramadhi, Ramadhi; Ramdani, Zulmi (Universitas Ahmad Dahlan, 2021)
Employees are an essential asset for the organization to advance and develop the organization to be more productive. This situation may achieve when employees in the organization have optimal performance. Many factors positively affect the performance of employees in the organization. This study aims to determine how much influence organizational commitment, work motivation and work discipline have on employee performance in PT. PLN (Persero) P3b Sumatera UPT Padang. Respondents who were involved in the study were 60 people who were selected using the saturated sample technique. The results showed that both partially and simultaneously, organizational commitment, work motivation, and work discipline had a significant and positive effect on employee performance. The coefficient of determination of the tested variables is .636. It shows that the percentage contribution of the variable organizational commitment, work motivation and work discipline to employee performance is 64.6%. In comparison, the remaining 35.4%Â determined by other variables not analyzed in this study's model. Thus, this study shows that the three tested variables must be an essential consideration for the organization to obtain optimal employee performance.